"You Throw Like a Girl!": Young Children's Gender Stereotypes About Object Control Skills. Issue 1 (2nd January 2023) - Taunton Miedema, Sally; Mulvey, Kelly Lynn; Brian, Ali
ABSTRACT: Purpose : Understanding if children hold stereotypes about motor skills, may partially explain differences in object control performance between young boys and girls. Therefore, the purpose of this study was to examine whether young boys and girls held stereotypes related to object control skills. Methods: Children (N = 84) ages three years four months to five years seven months (Mage = 4.6 years, SD = .58) completed the Test of Gross Motor Development—Second Edition and a modified version of the Children's Occupations, Activities and Traits Measure. Spearman Rho correlations examined associations between children's stereotypes and actual object control skills performance. We then examined differences between boys' and girls' gender stereotypes (three for each category) and object control skills via independent samples t-tests. Results: Results showed significant associations between gender stereotypes toward object control skills and actual object control skills for girls (ρ = −.31—−.53, p < .05) but not for boys (ρ = .10—.14, p > .05). Concurrently, girls showed significantly lower object control skills than boys ( t [82] = 2.01; p = .042, d = .44) as well as significantly higher gender stereotypes across all three categories ( p < .05, d = .54–1.77). Conclusion: These data indicated that girls, not boys, held gender stereotypes about object control skills in concert with lower object control skill performances. Future research should evaluate the impacts of an integrated gross motor intervention which seeks to change gender stereotypes and concurrently improve object control skill performance.